2018
DOI: 10.1039/c8nr00716k
|View full text |Cite
|
Sign up to set email alerts
|

Floating catalyst CVD synthesis of single walled carbon nanotubes from ethylene for high performance transparent electrodes

Abstract: We have developed the floating catalyst chemical vapor deposition (FCCVD) synthesis of single walled carbon nanotubes (SWCNTs) using C2H4 hydrocarbon as a carbon source and iron nanoparticles as the catalyst in an environmentally friendly and economical process. For the first time, ethylene was used as the only carbon source in FCCVD with N2 as the main carrier gas. No sulphur and less than 15% H2 in a N2 carrier gas were used. By varying the ferrocene concentration, the diameter of the SWCNTs was tuned in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 47 publications
8
70
0
1
Order By: Relevance
“…Moreover, the Fe SWCNTs were found randomly distributed from zig-zag to armchair edges with the mean chiral angle of 16.06±8.35 o having 61% of semiconducting nanotubes. This result is consistent with the ferrocene (Fe(C H ) ) based Fe SWCNTs using ethylene as a carbon source [63]. Hence, our result demonstrated that in the FC-CVD method, for the similar composition of catalyst particles, choice of the catalyst precursor has no significant effect in tuning the chirality distribution of SWCNTs.…”
Section: Tuning Chirality Of Swcnts With Catalyst Compositionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moreover, the Fe SWCNTs were found randomly distributed from zig-zag to armchair edges with the mean chiral angle of 16.06±8.35 o having 61% of semiconducting nanotubes. This result is consistent with the ferrocene (Fe(C H ) ) based Fe SWCNTs using ethylene as a carbon source [63]. Hence, our result demonstrated that in the FC-CVD method, for the similar composition of catalyst particles, choice of the catalyst precursor has no significant effect in tuning the chirality distribution of SWCNTs.…”
Section: Tuning Chirality Of Swcnts With Catalyst Compositionsupporting
confidence: 88%
“…It includes both through premade catalyst particles and in-situ catalyst synthesis processes. The growth has been observed in Fe, Co, Ni, Co-Ni catalysts from spark discharge generator with C2H4 as a carbon source [11] and from Fe catalyst particles obtained from in-situ decomposition of ferrocene (FeCp2) with C2H4 [63], C2H5OH [48] and CH4 as carbon sources (see Table 5.1). However, it's worth mentioning that in all these systems growth conditions of purely CNTs and graphene-CNTs hybrid material are different and one can get graphene-CNTs hybrid by precisely controlling growth parameters.…”
Section: Universality Of the Growth Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The hereby presented transistor array method is compatible with various types of FC‐CVD CNTs. To illustrate the compatibility, larger‐diameter FC‐CVD SWCNTs ( d ≈ 1.5 nm), grown with ethylene as the carbon feedstock, have been used . In the literature, the mean diameter of SWCNTs for measuring mobility is 1.5 nm or larger .…”
Section: Resultsmentioning
confidence: 99%
“…Thicker SWCNTs (mean diameter: 1.5 nm, length: 12.61 ± 4.48 µm) were grown using the FC‐CVD process with ferrocene as the catalyst precursor and ethylene as the carbon feedstock. A detailed description of the SWCNT growth system was published earlier …”
Section: Methodsmentioning
confidence: 99%